Developing the concept of roller conveyor systems using Industry 4.0 tools - Szentesi, Szabolcs; Tamás, Péter (Advanced Logistic Systems - Theory and Practice, 2023)
In the increasingly globalized world, markets are no longer competed for by individual companies, but by groups of companies and networks. Due to the challenges of globalization and sustainability, the management of the material flow has become a critical issue for organizations engaged in manufacturing activities, as the implementation of changed products due to new regulations into the existing material flow service network is a major challenge. Today, Industry 4.0 tools help solve challenges. The tools of Industry 4.0 and Logistics 4.0 offer many opportunities to professionals today, which are driven by several key basic technologies, such as simulation technologies, digital copies, Big Data technology. These technologies have a positive impact on the sustainability performance of material flow activities. Simulation models play an important role in the evaluation and planning of material flow strategies. The purpose of this study is to apply the methods used in Industry 4.0 and Logistics 4.0 in the design of material flow on a roller conveyor.